ANALISIS KESULITAN SISWA DALAM MENENTUKAN IDE POKOK PARAGRAF - Wulan Suci Ramadani; Usiono (JOURNAL SAINS STUDENT RESEARCH, 2025)
Learning Difficulties are a condition in which students face difficulties in meeting the required learning demands, low student interest in Indonesian language lessons contributes to this difficulty. Students who are less interested tend not to try to understand the material in depth. This study aims to determine students' difficulties in determining the main idea of ​​a paragraph. And to find out the factors that cause students to have difficulty in determining the main idea of ​​a paragraph. With the research method, namely Systematic Literature Review (SLR). The results of this analysis show that students' inability to read well, including spelling difficulties, is also a barrier. Students who are not yet fluent in reading often cannot capture important information in a paragraph. There are two factors that influence students' difficulties in determining the main idea of ​​a paragraph, namely internal factors and external factors.